Cytomorphometric evaluation of micronuclei in oral epithelial cells of smoker and non-smoker patients (Research, Society and Development, 2021)
Exfoliative cytology screening for genotoxicity is an important strategy for mitigating tobacco-induced carcinogenesis. The aim of this study was to determine the frequency of micronuclei in oral epithelial cells of smoking and non-smoking patients. Sixteen volunteers, of both sexes, 40-60 years old, with healthy oral mucosa were divided into smoking or non-smoking group. Cytological smears of buccal mucosa, lateral border of the tongue and floor of the mouth stained by Pap stain allowed evaluation of 4800 microscopic images. Frequencies of micronucleated cells (MNC) and micronuclei/cell (MN/C) were compared by group, anatomical region, sex and age range, using the two-way ANOVA test followed by Tukey (p